Fishery characteristics and stock status of Lethrinus lentjan in selected fishing areas along the Kenya Coast - Ketterer Akinyi, Susan; Nzaka Munga, Cosmas; Kalama mkare, Thomas (Multidisciplinary Journal of Technical University of Mombasa, 2023)
Small scale fisheries is dominant along the Kenya coast characterised by multispecies, multigear and multi-fleet and therefore prone to over-exploitation. The success of fisheries sustainable management is dependent on life history traits of the target stock. This study was aimed to characterize the small scale lethrinus fishery as well as determine its current stock status. Monthly shore-based catch assessments for fisheries and biological data were collected from October 2020 to September 2021 from selected fish landing sites along the Kenya coast. A total of 22 species belonging to the genus Lethrinus were recorded over the study period. Overall Msambweni fishing area had the highest landings of the genus Lethrinus, accounting for more than 69%, and the overall contribution of Lethrinus lentjan to the overall total fish landings was 25%. Female individuals of L. lentjan were more abundant than males, with an overall sex ratio of 1:1.53, which differed significantly from the expected ratio of 1:1. Lethrinus lentjan recorded a negative allometric growth with an asymptotic length (L∞) and growth coefficient (K) of 51 cm and 0.46 y-1, respectively. The total mortality (Z) was 2.07, the natural mortality (M) was 0.963, and the fishing mortality (F) was 1.10 with an exploitation rate of 0.53. The recorded E value of 0.53, in this study, was slightly higher than the optimum exploitation rate of E = 0.5, indicating an exploited fishery. Therefore, the study recommends that the management system of this fishery should be revised carefully.
Keywords: Relative condition factor; Length-weight relationship; Stock status; Exploitation rate; Kenya coast